2017
DOI: 10.1159/000485355
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 is Upregulated by Decreased miR-122 Expression in Iron-Overload-Induced Hepatic Inflammation

Abstract: Background/Aims: Iron overload (IO) is accompanied by hepatic inflammation. The chemokine (C-C motif) ligand 2 (CCL2) mediates inflammation, and its overexpression is associated with IO. However, whether IO results in CCL2 overexpression in the liver and the underlying mechanisms are unclear. Methods: We subjected mice to IO by administering intraperitoneal injections of dextran-iron or by feeding mice a 3% dextran-iron diet to observe the effects of IO on miR-122/CCL2 expression through real-time qPCR and Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…SOCS1 can be activated by EpoR stimulation and plays a negative regulatory effect on inflammation induced by cytokine [24]. With the MRI T2* technique, we found that the levels of iron deposition in the liver and heart of experience group patients were increased, which would affect the function of heart and liver and induce inflammatory reaction [25]. It is speculated that that a substantial increase in sEPO and inflammatory mediators could induce the increase of SOCS1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…SOCS1 can be activated by EpoR stimulation and plays a negative regulatory effect on inflammation induced by cytokine [24]. With the MRI T2* technique, we found that the levels of iron deposition in the liver and heart of experience group patients were increased, which would affect the function of heart and liver and induce inflammatory reaction [25]. It is speculated that that a substantial increase in sEPO and inflammatory mediators could induce the increase of SOCS1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…It was reported that pre-treatment with IRE1α inhibitor reduced pro-inflammatory cytokines production in tumor necrosis factor (TNF)-receptor-associated periodic fever syndrome (TRAPS) dermal fibroblasts (DFs) ( Harrison et al, 2018 ). On the other hand, these inflammatory cytokines were also the downstream target genes of miR-122 ( Hsu et al, 2012 ; Nakamura et al, 2015 ; Yin et al, 2016 ; Tang et al, 2017 ). In the present study, the result showed that STF-083010 evidently inhibited the upregulation of hepatic α-SMA, Col1α1 and Col1α2 in mice, but these also may be attributed to HSCs expression and the fact that STF-083010 alleviates liver injury by inhibiting CCl 4 -mediated hepatocyte death.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-122 inhibition increases the amount of mRNA transcribed by genes that control systemic iron levels, such as HFE, HJV, bone morphogenetic protein receptor type 1A (Bmpr1a), and HAMP ( Castoldi and Muckenthaler, 2012 ). Li et al (2017) and Tang et al (2017) have demonstrated that iron overload in mice induces the down-regulation of miR-122. Also, in patients with iron overload disorders, it was observed that miR-122 was decreased.…”
Section: Discussionmentioning
confidence: 99%